Accelerating cutaneous healing in a rodent model of type II diabetes utilizing non-invasive focused ultrasound targeted at the spleen - Morton, Christine; Cotero, Victoria; Ashe, Jeffrey; Ginty, Fiona; Puleo, Christopher (Frontiers in Neuroscience, 2022)
Healing of wounds is delayed in Type 2 Diabetes Mellitus (T2DM), and new treatment approaches are urgently needed. Our earlier work showed that splenic pulsed focused ultrasound (pFUS) alters inflammatory cytokines in models of acute endotoxemia and pneumonia via modulation of the cholinergic anti-inflammatory pathway (CAP) (ref below). Based on these earlier results, we hypothesized that daily splenic exposure to pFUS during wound healing would accelerate closure rate via altered systemic cytokine titers. In this study, we applied non-invasive ultrasound directed to the spleen of a rodent model (Zucker Diabetic Sprague Dawley (ZDSD) rats) of T2DM with full thickness cutaneous excisional wounds in an attempt to accelerate wound healing via normalization of T2DM-driven aberrant cytokine expression. Daily (1x/day, Monday-Friday) pFUS pulses were targeted externally to the spleen area for 3 minutes over the course of 15 days. Wound diameter was measured daily, and levels of cytokines were evaluated in spleen and wound bed lysates. Non-invasive splenic pFUS accelerated wound closure by up to 4.5 days versus sham controls. The time to heal in all treated groups was comparable to that of healthy rats from previously published studies (ref below), suggesting that the pFUS treatment restored a normal wound healing phenotype to the ZDSD rats. IL-6 was lower in stimulated spleen (-2.24±0.81 Log2FC p=0.02) while L-selectin was higher in the wound bed of stimulated rodents (2.53±0.72 Log2FC p=0.003). In summary, splenic pFUS accelerates healing in a T2DM rat model, demonstrating the potential of the method to provide a novel, non-invasive approach for wound care in diabetes.